(untitled) (Papeles, 2021)
In this article of theoretical reflection, the following hypothesis is defended: conventional economists seek to control rational behaviors and expected behaviors of individuals with predictable, routine choices devoid of tragic and radical choices. They are concerned with studying monotonous and probable fluctuations and omit the great turbulences (tragic and unlikely phenomena, that is, black swans) and focus on normalized individuals, that is, devoid of freedom, passions and morality. Addressing this discussion may have positive repercussion for economics teaching and research.